Aiming for the Sweet Spot: Glyco-Immune Checkpoints and γδ T Cells in Targeted Immunotherapy - Bartish, Margarita; del Rincón, Sonia V.; Rudd, Christopher E.; Saragovi, H. Uri (Frontiers in Immunology, 2020)
Though a healthy immune system is capable of recognizing and eliminating emergent cancerous cells, an established tumor is adept at escaping immune surveillance. Altered and tumor-specific expression of immunosuppressive cell surface carbohydrates, also termed the “tumor glycocode,” is a prominent mechanism by which tumors can escape anti-tumor immunity. Given their persistent and homogeneous expression, tumor-associated glycans are promising targets to be exploited as biomarkers and therapeutic targets. However, the exploitation of these glycans has been a challenge due to their low immunogenicity, immunosuppressive properties, and the inefficient presentation of glycolipids in a conventional major histocompatibility complex (MHC)-restricted manner. Despite this, a subset of T-cells expressing the gamma and delta chains of the T-cell receptor (γδ T cells) exist with a capacity for MHC-unrestricted antigen recognition and potent inherent anti-tumor properties. In this review, we discuss the role of tumor-associated glycans in anti-tumor immunity, with an emphasis on the potential of γδ T cells to target the tumor glycocode. Understanding the many facets of this interaction holds the potential to unlock new ways to use both tumor-associated glycans and γδ T cells in novel therapeutic interventions.